Progress, challenges and opportunities for HIV prevention and control among high risk groups: a public health perspective - Gupta, Renu; Khurana, Sarbjeet; Singh, Ravinder (International Journal of Medicine, 2014)
Aim of the study: To study various factors linked to the prevention and control of HIV-AIDS in the high risk groups in India. Objective of the study: 1) To study the socio-cultural and political obstacles in the prevention and control of HIV-AIDS in India. 2) To study the factors responsible for poor access of antiretroviral therapy (ART) in India. Methodology: The relevant published literature was searched for studying various factors in the prevention and control of HIV-AIDS as well as for the factors responsible for the poor access of ART in India. Observations: There are various socio-cultural issues/obstacles in prevention of HIV-AIDS in high risk group for e.g., gender inequality, power inequalities and male dominance; condom use believed to be in conflict with the cultural importance for procreation; poverty, illiteracy, increase in migrant population and unemployment; poor knowledge and awareness of reproductive and sexual health and sexuality; emergence of new urban sub-culture and physical or mental abuse at a young age. Lack of awareness and access to health care; misconceptions; stigma and discrimination, leading to secrecy of their high risk behavior and hence the further spread of the disease. There are various political obstacles viz; HIV-AIDS control program has a focus on short term goals rather than long term sustainable achievements; minimal involvement of people living with HIV and AIDS in policy formulation and no political initiatives taken for family centered approach; lack of rights approach and control program lacks planning with regard to the structural factors existing in the country. There are various factors responsible for poor access of the population groups for ART viz; social factors like lack of awareness about HIV and availability of ART; long waiting hours at the ART centers etc. Economic factors responsible for poor access of the population groups for ART are the costs of travelling to the clinic; shortage of doctors/paramedics for prescribing medicines, shortage of personnel/ trained counselors, shortage of testing facilities and inadequate laboratory support. Political factors leading to poor access of ART are lack of political initiative for expansion of services, submitting documents such as ration card/voter ID has been made mandatory for treatment, lack of consistency and coordination across services and the control program not reaching to the marginalized groups. Keywords: HIV, AIDS, High Risk Groups, Socio-Cultural Factors, Political Factors, ART, Task Shifting.